(3eNJUQ GdfYeI GdcHQi Ydi GdYGde HOhdI SjO Hfj BOe Udi Gddg Ydjg hSdes - (3GdngrjnJej GdSYOj Gdecj, CHh GdYHGS, TgGH GdOjf, CMeO Hf eMeO Hf Ydj Hf MLQ, J (B974 (3g`s ((3OjH GdQcGHs)
(3ChdgG (B:s
(3GdMeO ddg GdPj TQa gPG GdYGde HehdO SjO hdO BOe hced Hg SYhO GdCfHjGA hGdeQSdjfs
(3BNQgG (B:s
(3aCNPgG GdeNGV hGTJO HgG GdCeQ hcCfgG eSJfOI Edi fSGA hcKQf YdjgG MJi cCfgf eYgG aj GdHjJ aMjfFP hdOJg Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 234s
(3eYLe GdeDdajf(B: 1 / 293 (3, (B294s
(3EjVGM Gdecfhf(B: 2 / 661s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs